The different effects of low-level laser therapy before and after overinstrumentation on the expression of substance P and interleukin-10 - Sri Kunarti; Devi Eka Juniarti; Yulianti Kartini Sunur; Meidi Kurnia Ariani (Elsevier, 2023)
Background: One of the causes of endodontic flare-ups is overinstrumentation during canal preparation. In general, to reduce the level of pain and swelling that is caused by endodontic flare-ups, patients it has taken analgesics and antibiotics after treatment. However, some patients have been reported to have allergic reactions to nonsteroidal anti-inflammatory drugs. Lasers have been reported to be significantly effective in reducing pain and inflammation after root canal treatment. Low-level laser therapy (LLLT) 650 nm pre- or post-conditioning is widely used as a therapy. Objective: This study investigated the effect of pre- or post-conditioning with a 650 nm diode laser to reduce pain caused by overinstrumentation Methods: Thirty incisor teeth from Wistar rats were overinstrumented and exposed to a 650 nm diode laser before or after overinstrumentation and then divided into six groups. Groups I and II were control groups (30 and 120 min), groups III and IV were precondition groups (30 and 120 min) and Groups V and VI were postcondition groups (30 and 120 min). Immunohistochemical analysis was conducted to check the expression of substance P and interleukin-10 (IL-10) Result: The expression of substance P in the precondition LLLT groups was significantly lower than that in the control and postcondition groups. On the other hand, the expression of IL-10 in the precondition LLLT groups was significantly higher than that in the control and postcondition groups. Conclusion: There was a decrease in pain after preconditioning laser diode 650 nm exposure.